Evaluasi Implementasi Program Parenting dalam Peningkatkan Layanan Kelas Pertemuan Orangtua - Sri Wahyuni; Juhri AM; Fatqul Hajar Aswad (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
Parental involvement in early childhood education is a key factor in supporting the success of holistic learning processes. However, in many early childhood education institutions, including TK Baitussalam Pringsewu, the implementation of parenting programs has not been optimal, as indicated by low parental participation and limited communication between schools and families. This study aims to comprehensively evaluate the implementation of parenting programs in supporting parental involvement through the Parent Meeting Class (KPO) service using the CIPP evaluation model (Context, Input, Process, Product). This research employed a qualitative approach with a case study design. Informants included the school principal, parenting coordinator/teachers, and parents. Data collection was carried out through in-depth interviews, observations, and documentation. Thematic analysis was conducted based on the CIPP components. The findings reveal that in terms of context, the parenting program is considered relevant to local needs. However, in the input aspect, there are still limitations in facilitator competencies and variations in parental participation. The implementation process is conducted regularly and is relatively participatory, but it lacks a sustainable evaluation system. The product of the program shows positive impacts on improving parenting knowledge, communication between school and family, and parental engagement in supporting children’s learning at home. This study contributes to improving a more reflective and contextual implementation model for parenting programs in early childhood education settings. Recommendations are focused on strengthening adaptive parenting materials, providing ongoing facilitator training, and developing a feedback-based monitoring system to enhance the effectiveness of the KPO service.